Peripheral Arterial Disease among Diabetic Patients in Dr. Hasan Sadikin General Hospital Bandung 2012 - Feriska Fairuz Azkiyah; Teguh Marfen Djajakusumah; RA. Retno Ekowati (Althea Medical Journal, 2015)
Background: As one of the most devastating complication in diabetes mellitus, peripheral arterial disease is still under detected in health care services. This study aimed to reveal the frequency of peripheral arterial disease in diabetic patients in Endocrine and Metabolism Clinic in Dr. Hasan Sadikin General Hospital Bandung.Methods: A cross sectional descriptive study was conducted during the period of October to November 2012 in Endocrine and Metabolism Clinic in Dr. Hasan Sadikin General Hospital Bandung. As many as 54 patients who met the inclusion criteria and agreed to participate in this study signed the informed consent form then underwent history taking, simple physical examination of lower extremities, and Ankle-Brachial Index (ABI) measurement. Normality of the data distribution was calculated by Kolmogorov-Smirnov test.Results: From a total 54 diabetic patients enrolled, it was found 18 cases of peripheral arterial disease, consisted of 10 patients with Ankle-Brachial Index measurement ≤0.9 and 8 patients with Ankle-Brachial Index measurement >1.4. Most of the cases occurred in the elderly group (>60 years old) and had been diagnosed diabetes less than 10 years.Conclusions: The frequency of peripheral arterial disease in diabetic patients attended Dr. Hasan Sadikin General Hospital Bandung is 33.3% and more prevalent in elderly patients. It occurred mostly in patients diagnosed with diabetes less than 10 years. [AMJ.2015;2(1):287–90]